A Functional Plasminogen Assay Utilizing the Potentiating Effect of Fibrinogen to Correct for the Overestimation of Plasminogen in Pathological Plasma Samples - Gram, Jørgen; Jespersen, Jørgen (Thrombosis and Haemostasis, 1985)
An overestimation of the plasminogen concentration occurs in patients with elevated levels of fibrin degradation products (fdp) and/or fibrinogen, when using assays based on the activation of plasminogen by streptokinase (Sk) followed by the hydrolysis of a synthetic chromogenic substrate. This source of error could be overcome by addition of fibrinogen in excess to the plasminogen assay thereby obtaining maximum stimulation of the Sk-plasminogen complex. The late degradation products of fibrinogen and fibrin, Dcate and Ddimer, respectively, had no potentiating effect on the Sk-plasminogen complex. The modified assay was designed as a manual method or for a centrifugal analyzer. The excellent reproducibility is illustrated by the coefficient of variation (CV) within series being 1.3% (n = 24) and from day to day being 1.9% (n = 20).
Keywords: Plasminogen assay; Sk-plasminogen; Fibrinogen; Fibrin degradation products; Amidolytic method